Anatomical region-dependent enhancement of 3-dimensional chondrogenic differentiation of human mesenchymal stem cells by soluble meniscus extracellular matrix. (February 2017) - Rothrauff, Benjamin B.; Shimomura, Kazunori; Gottardi, Riccardo; Alexander, Peter G.; Tuan, Rocky S.
Graphical abstract: Abstract: Extracellular matrix (ECM) derived from decellularized tissues has been found to promote tissue neogenesis, most likely mediated by specific biochemical and physical signaling motifs that promote tissue-specific differentiation of progenitor cells. Decellularized ECM has been suggested to be efficacious for the repair of tissue injuries. However, decellularized meniscus contains a dense collagenous structure, which impedes cell seeding and infiltration and is not readily applicable for meniscus repair. In addition, the meniscus consists of two distinct anatomical regions that differ in vascularity and cellular phenotype. The purpose of this study was to explore the region-specific bioactivity of solubilized ECM derived from the inner and outer meniscal regions as determined in 2D and 3D cultures of adult mesenchymal stem cells (MSCs). When added as a medium supplement to 2D cultures of MSCs, urea-extracted fractions of the inner (imECM) and outer meniscal ECM (omECM) enhanced cell proliferation while imECM most strongly upregulated fibrochondrogenic differentiation on the basis of gene expression profiles. When added to 3D cultures of MSCs seeded in photocrosslinked methacrylated gelatin (GelMA) hydrogels, both ECM fractions upregulated chondrogenic differentiation as determined by gene expression and protein analyses, as well as elevated sulfated glycosaminoglycan sGAG content, compared to ECM-free controls. The chondrogenic effect at day 21 was most pronounced with imECM supplementation, but equivalent between ECM groups by day 42. Despite increased cartilage matrix, imECM and omECM constructs possessed compressive moduli similar to controls. In conclusion, soluble meniscal ECM may be considered for use as a tissue-specific reagent to enhance chondrogenesis for MSC-based 3D cartilage tissue engineering. Statement of Significance: The inner region of the knee meniscus is frequently injured and possesses a poor intrinsic healing capacity. Solubilized extracellular matrix (ECM) derived from decellularized meniscus tissue may promote homologous differentiation of progenitor cells, thereby enhancing fibrocartilage formation within a meniscal lesion. However, the meniscus possesses regional variation in ultrastructure, biochemical composition, and cell phenotype, which may affect the bioactivity of soluble ECM derived from different regions of decellularized menisci. In this study, we demonstrate that urea-extracted fractions of ECM derived from the inner and outer regions of menisci enhance chondrogenesis in mesenchymal stem cells seeded in 3-dimensional photocrosslinkable hydrogels and that this effect is more strongly mediated by inner meniscal ECM. These findings suggest region-specific bioactivity of decellularized meniscal ECM.